2014
DOI: 10.1111/bju.12449
|View full text |Cite
|
Sign up to set email alerts
|

Should centralized histopathological review in penile cancer be the global standard?

Abstract: • Newly diagnosed squamous cell carcinomas (SCC) of the penis, including squamous cell carcinoma in situ (CIS), from biopsy specimens were referred from 15 centres to the regional supra-network multidisciplinary team (Sn-MDT) between 1 January 2008 and 30 March 2011.• Biopsy histology reports and slides from the respective referring hospitals were reviewed by the Sn-MDT pathologists.• The biopsy specimens' histological type, grade and stage reported by the Sn-MDT pathologist were compared with those given in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 3 publications
2
15
0
2
Order By: Relevance
“…3 reported above (20). In 2012, the first results of the network in the East Midlands in UK showed an increase in the number of cases discussed since its formation and a trend towards more conservative surgery (53).…”
Section: A N U S C R I P Tmentioning
confidence: 96%
See 1 more Smart Citation
“…3 reported above (20). In 2012, the first results of the network in the East Midlands in UK showed an increase in the number of cases discussed since its formation and a trend towards more conservative surgery (53).…”
Section: A N U S C R I P Tmentioning
confidence: 96%
“…Moreover, the role of surgery both as post-chemotherapy option and as primary treatment (RPLND) in early stages of disease is commonly recommended, as it is associated with a better outcome (17). A UK experience (20) showed that after histology review, pathology diagnoses significantly changed, with 31% of cases receiving a reclassification. The changes were deemed to be critical in 60.4% cases:…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Despite appropriate treatment, the 5-year survival is only 50% in an overall stage-independent analysis, and only 27% in patients with node-positive disease [ 4 ]. A multidisciplinary approach, preferably in high-volume specialized centers, is therefore imperative for developing an optimal management plan, helping to standardize care and facilitating recruitment to clinical trials [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the positive impact of COC on PC management, centralization of histopathological review of PC specimens is beneficial for patient care. Tang et al [8] rereviewed 155 histopathological diagnoses of penile squamous cell carcinoma or carcinoma in situ that were referred for centralized histopathological review in one of the UK PC supranetwork hospitals. Any discrepancy between the referring histopathological diagnosis and the one reported by the supranetwork pathologist was recorded.…”
mentioning
confidence: 99%